Markups in the euro area and the US over the period 1981-2004: a comparison of 50 sectors - Rebekka Christopoulou; Philip Vermeulen (European Central Bank (ECB), 2008)
This paper provides estimates of price-marginal cost ratios or markups for 50 sectors in 8 euro area countries and the US over the period 1981-2004. The estimates are obtained applying the methodology developed by Roeger (1995) on the EU KLEMS March 2007 database. Five stylized facts are derived. First, perfect competition can be rejected for almost all sectors in all countries; markup ratios are generally larger than 1. Second, average markups are heterogenous across countries. Third, markups are heterogeneous across sectors, with services having higher markups on average than manufacturing. Fourth, services sectors generally have higher markups in the euro area than the US, whereas the pattern is the reverse for manufacturing. Fifth, there is no evidence that there is a broad range change in markups from the eighties to the nineties.
Keywords: D3; L11; 330; marginal cost; markup; price; Branchenentwicklung; Preisniveau; Preismanagement; Mark-up Pricing; Grenzkostenpreis; EU-Staaten; USA